(untitled) (Research, Society and Development, 2021)
The etiologic agent of dengue is an arbovirus, with four different serotypes (DENV 1, 2, 3 and 4), transmitted by the Aedes aegypti mosquito. All serotypes can cause several clinical manifestations, ranging from mild symptoms to more severe symptoms, even leading to death. This study aimed to analyze the cases of dengue in Piauí, reported between 2014 and 2020, and to assess the frequency of laboratory tests essential for the diagnosis of this arbovirus in the state. In this context, the study is a descriptive, retrospective and cross-sectional epidemiological research, with a quantitative approach, with data collection on the digital platform of Diseases and Conditions of Notification of the National System of Information on Diseases and Notification (SINAN/DATASUS ). It was found that 38,093 cases of dengue were registered in the state. It was observed that out of the total number of cases, the majority (57.49%) occurred in women, and that the most affected population was young adults (20-39 years). When analyzing parameters related to the diagnosis of dengue, it was verified the recording of data as "not performed" or "ignored/blank" overlapping the exams performed (positive/negative/inconclusive), as in the detection of IgM antibodies, ELISA serological tests and viral isolation. The DENV-1 and DENV-2 serotypes were the most detected in Piauí. Therefore, it is observed that the clinical-epidemiological diagnosis has been superimposed on the performance of diagnostic tests. However, it is noteworthy that the performance of laboratory tests allows a precise and specific monitoring of the evolution and spread of the infection in the state.